Coral and Coral Reefs - Huxley, Thomas Henry, 1825-1895 (Salt Lake City, UT : Project Gutenberg, 2001)
"Coral and Coral Reefs" by Thomas Henry Huxley is a scientific publication from the late 19th century that explores the structure and origin of corals and coral reefs. This book delves into the biological and geological processes that contribute to the formation of these marine structures, emphasizing the relationship between coral polyps and the materials that make up their skeletons. Huxley's work is significant in the study of marine biology and ecology, providing insight into coral systems and their importance to oceanic environments. The book begins by distinguishing between different types of coral, specifically red and white coral, and explains the biological structure of sea anemones, which are closely related to corals. Huxley details the various reproductive methods of coral polyps, including fission and budding, and describes how these processes lead to the formation of large coral structures. The text further examines the different types of coral reefs, such as fringing reefs, barrier reefs, and atolls, linking their development to geological processes like subsidence and sea level changes. Huxley's observations, supported by examples like the coral formations around the island of Mauritius, lead to significant conclusions about the long-term evolution of coral reefs and their implications for understanding the history of the Earth. (This is an automatically generated summary.)
Release date is 2001-11-01
Produced by Amy E. Zelmer, and David Widger
Keywords: Coral reefs and islands